Ответ:
Объяснение:
1) 8a(4+3a)-12a(2a+2) => раскрываем скобки и приводим подобные слагаемые
1) 32a+24a^2 -24a^2-24a=32a-24a=8a => (a=-0.5)=>
8a=8*(-0.5) = -4.
-----------
2) (3x+5)(x-2)-(x-3)(2x+1) => раскрываем скобки и приводим подобные слагаемые
3x^2-6x+5x-10 - 2x^2-x+6x+3=x^2+4x-7 => при x=-6 =>
(-6)^2 + 4*(-6) - 7=36-24-7 = 5.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
1) 8a(4+3a)-12a(2a+2) => раскрываем скобки и приводим подобные слагаемые
1) 32a+24a^2 -24a^2-24a=32a-24a=8a => (a=-0.5)=>
8a=8*(-0.5) = -4.
-----------
2) (3x+5)(x-2)-(x-3)(2x+1) => раскрываем скобки и приводим подобные слагаемые
3x^2-6x+5x-10 - 2x^2-x+6x+3=x^2+4x-7 => при x=-6 =>
(-6)^2 + 4*(-6) - 7=36-24-7 = 5.